MENYOAL KRITIK IGNAZ GOLDZIHER TERHADAP AL-QUR’AN DALAM KITAB MAZHAHIB AL-TAFSIR AL-ISLAMI - Raihan Raihan; Syafieh Syafieh (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
Ignaz Goldziher is one of the orientalist figures who criticize various Islamic studies. Especially regarding the Qur’an, which he put in his magnum opus, namely the book Mazhahib Al-Tafsir Al-Islami. In the book, he aggressively criticizes the authenticity of the Qur'an. He thought that the emergence of qira'at was due to the paleography of the ancient Qur'an which did not have dots and vowels, so he judged that qira'at al-Qur'an was ijtihad, not tauqifi. The purpose of this study is to provide a more in-depth explanation that the criticism made by Goldziher is a big mistake so that it can minimize confusion and worries from the general public. This study uses a qualitative method with a literature study approach. The results of the study conclude that Ignaz Goldziher's confusion in thinking arises because he assumes that the Qur'an comes from a text like the Bible. it is the text that was born from the Qur'an, because the guidelines for qira'at al-Qur'an are not writing but history. He forgot that Muslims maintain the authenticity of the Qur'an using oral traditions that are maintained through rote memorization and the transmission process of the sanad Which is mutawatir from generation to generation. So it is impossible to say that there is confusion in the Qur'an.